Determinants and Consequences of High Fertility : A Synopsis of the Evidence - World Bank (World Bank, Washington, DC, 2017)
In the six decades since 1950, fertility has fallen substantially in developing countries. Even so, high fertility, defined as five or more births per woman over the reproductive career, characterizes 33 countries. Twenty-nine of these countries are in Sub-Saharan Africa. High fertility poses health risks for children and their mothers, detracts from human capital investment, slows economic growth, and exacerbates environmental threats. These and other consequences of high fertility are reviewed in the first half of this paper. Recognizing these detrimental consequences motivates two inter-related questions that are addressed in the second half of the paper: Why does high fertility persist? And what can be done about it? The high-fertility countries lag in many development indicators, as reflected for example in their rate of progress toward achievement of the Millennium Development Goals (MDGs). These countries have also received less development assistance for population and reproductive health than countries more advanced in their transitions to lower fertility, and the assistance they did receive increased only marginally from 1995 to 2007, a period during which commitments to both health and HIV/AIDS rose substantially.